Schistosomiasis malayensis-like infection among the Penan and other interior tribes (Orang Ulu) in upper Rejang River Basin Sarawak Malaysia - Sagin, DD; Ismail, G.; Fui, JN; Jok, JJ (Southeast Asian Ministers of Education Organisation., 2001)
A serosurvey of various indigenous interior tribes (Orang Ulu) in upper Rejang River Basin Sarawak Malaysia, the site of a multibillion Ringgit hydroelectric power project, found 6.8% of the individual surveyed were seropositive for schistosomiasis, as determined by ELISA method using the soluble egg antigen of Schistosoma malayensis Baling strain. In all age group, the seroprevalence rate is higher (9.5%) in males than in females (4.5%) except for the 31-40 age group. Seroprevalence of schistosomiasis was found to increase with age with the above 60 age group having the highest rate followed by the 31-40 age group. Seroprevalence rate among the tribes ranges from 4.1% among the Penan to 11.6% among the Kajang. There was no seroevidence of schistosomiasis among the Ukits. A snail survey found four snail species including Brotia species, the intermediate host of the lung fluke Paragonimus westermani, however no schistosome snail host was identified. Although schistosomiasis malayensis-like infection may be endemic in the area, its public health significance remains undetermined.